Penguatan Kapasitas Kepemimpinan Institusional Dalam Transformasi Administrasi Negara Guna Meningkatkan Daya Saing Nasional - Fernanda, Desi (Jurnal Borneo Administrator, 2007)
During new order regime, indonesia has exprienced both state failures and market failures which, fortunately, inspiring the emergence of civil society movement.